RESULTS OF ARCHEOGRAPHIC RESEARCH IN DAGESTAN IN 2017―2018 - Navruzov, Amir Ramazanovic (History, Archeology and Ethnography of the Caucasus, 2019)
The article deals with the results of archeographic studies, carried out by the Institute of history, archeology and ethnography of DSC RAS in 2017-2018. The introductory part covers methods of an archeographic work in examining manuscripts: each manuscript is described in detail, according to the description plan approved by the Institute’s Department of Oriental Studies, and includes positions that give a detailed description of a descriptive unit under study and which forms the basis of archeographic research. The main body reviews archeographic studies in 2017 in 4 regions of Dagestan, where manuscripts were discovered: 3 new manuscript collections in Akushinsky district, 2 collections in Levashinsky district, 2 collections in Kayakentsky district, 10 collections in Karabudakhentsky one – overall 17 collections, including manuscripts and a large number of old-printed books. Among the arabographic materials, there are findings in following branches of medieval Arabic science: Quran and Quran disciplines, Quran commentaries, tajwid (the art of reading Quran), Arabic grammar, rhetoric, lexicography, fiqh, dogmatics, al-sira, poetics, propaedeutics, hadith, logics, astronomy. Among Turkic materials, the most interesting one is the arabographic manuscript “Derbend-nameh” with texts, mainly on history, in the Kumyk language. The total number of manuscripts and old-printed books found and studied in 2017 is more than 300 units. They date from the 15th to the 19th centuries. In 2018, the nature and focus of archeographic research changed: the task was set to narrow the gap between field and traditional archaeography. In this regard, archeographic research in that year was directed, along with searching and collecting of material, mainly for research, preparation for publication and publication of manuscript collections – in particular, of two private manuscript collections of the Keleb region of the Shamil district of the Republic of Dagestan: the collection of Gitinmagomedov Usman-Hadji from the village of Hinda and the collection of Hasanov Karimula from Somoda village. .